Evaluation of perception of quality of life of disabled athletes - Bartosz Bolach; Tetyana. Prystupa (Physical Education of Students, 2014)
Purpose: To evaluate the perception of quality of life for athletes - disabled, participating in individual and team Paralympic sports. Material: The study involved 32 athletes sports club "Start" in Wroclaw in 2013, engaged in individual sports: swimming, weightlifting, powerlifting (powerlifting) and command: wheelchair basketball and volleyball in a sitting position. Results: Studies have proven that sports people with physical disabilities have a positive effect on the quality of their lives. Conclusions: 1. Study aspects of perception of quality of life is a complex issue, but deserves proper attention and appropriate force to study it. 2. Athletes - Disabled involved both individual and team sports, the perception of quality of life is average.